Water electrolyte promoted oxidation of functional thiol groups. (15th April 2016) - Lauwers, K.; Breynaert, E.; Rombouts, I.; Delcour, J.A.; Kirschhock, C.E.A.
Graphical abstract: Highlights: Functional thiol groups oxidized faster in common tap water than in ultrapure water. The impact of water electrolyte composition on thiol oxidation kinetics was studied. Calcium chloride increased oxidation rate of glutathione but not that of cysteine. Electrolytes can impact bread (dough) characteristics and industrial biopolymers. Abstract: The formation of disulfide bonds is of the utmost importance for a wide range of food products with gluten or globular proteins as functional agents. Here, the impact of mineral electrolyte composition of aqueous solutions on thiol oxidation kinetics was studied, using glutathione (GSH) and cysteine (CYS) as model systems. Interestingly, the oxidation rate of both compounds into their corresponding disulfides was significantly higher in common tap water than in ultrapure water. The systematic study of different electrolyte components showed that especially CaCl2 improved the oxidation rate of GSH. However, this effect was not observed for CYS, which indicated a strong impact of the local chemical environment on thiol oxidation kinetics.